2013
DOI: 10.1177/1741143213499256
|View full text |Cite
|
Sign up to set email alerts
|

The effect of school-leader support and participation in decision making on teacher collaboration in Dutch primary and secondary schools

Abstract: Over the last three decades, the concept of teacher collaboration has been embraced as a promising concept in the sphere of educational policy and educational research. Teacher collaboration is now considered crucial to strengthening the position of teachers, shaping their professional space and improving their professionalism. However, the concept of teacher collaboration lacks consensus: both its definitions and its purpose are the subject of discussion and criticism. Against this background, we present a th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
30
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 48 publications
5
30
0
1
Order By: Relevance
“…This result is in line with and empirically supports theoretical frameworks stressing collaborative processes and lesson development as main components of inclusive leadership (Blackmore 2006;Dorczak 2011;Dyson 2010;Kugelmass and Ainscow 2004). Moreover, it is in line with previous empirical studies investigating the relationship between leadership, collaboration and lesson development (Goddard et al 2015;Gumus, Bulut, and Bellibas 2013;Honingh and Hooge 2014;Pietsch et al 2016). With respect to transformational leadership the study showed, however, that the positive effect is only due to the positive impact transformational leadership had on the provision of structures for collaboration.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…This result is in line with and empirically supports theoretical frameworks stressing collaborative processes and lesson development as main components of inclusive leadership (Blackmore 2006;Dorczak 2011;Dyson 2010;Kugelmass and Ainscow 2004). Moreover, it is in line with previous empirical studies investigating the relationship between leadership, collaboration and lesson development (Goddard et al 2015;Gumus, Bulut, and Bellibas 2013;Honingh and Hooge 2014;Pietsch et al 2016). With respect to transformational leadership the study showed, however, that the positive effect is only due to the positive impact transformational leadership had on the provision of structures for collaboration.…”
Section: Discussionsupporting
confidence: 88%
“…Two different, yet related, sets of leadership practices were focused: transformational leadership and instructional leadership. In line with prior research, we found medium to strong connections between school leadership and collaboration (Pietsch et al 2016;Honingh and Hooge 2014;Goddard et al 2015). However, we did not investigate the actual collaboration but the structures provided by the school leader for collaboration.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…In doing so, however, they abdicate as leaders (Hult et al 2016). It is difficult for teachers, who have busy days teaching students, to develop professionally without leader support and clear priorities and expectations (Honingh and Hooge 2014). Professional work develops through collective work and a joint knowledge base that also leaders adhere to.…”
Section: Discussionmentioning
confidence: 99%
“…Honingh and Hooge (2014) claim that in past research, teacher collaboration has mostly been regarded as an intermediate variable, leading to a lack of evidence on both the extent to which teachers collaborate and the aspects that influence teacher collaboration (Honingh and Hooge, 2014). As a response, they carry out secondary data analyses on teacher collaboration in both primary and secondary schools in the Netherlands with the aim to analyze the extent to which "teachers in primary and secondary schools collaborate, and which school and teacher characteristics affect their collaboration" (Honingh and Hooge, 2014, p. 76).…”
Section: Leadership Practices and Organizational Frameworkmentioning
confidence: 99%